Implementation of Regional Tax Payments via Standard Indonesian Quick Response (Qris) at the Regional Revenue Agency of Palopo City - Muh. Yusril (Pustaka Digital Indonesia, 2023)
QRIS is a payment system that is the QR Code standard for digital payments via electronic applications so that transactions can be more efficient. QRIS was developed by Bank Indonesia together with the payment system industry which can process transactions quickly, easily and safely. The aim of this research is to determine the benefits of implementing regional tax payments through QRIS at the Regional Revenue Agency of Palopo City. The research object of this final assignment is